De vlam : weekblad voor vrijheid en cultuur (Amsterdam, 1945)
"Bibliotheek Camille HuysmansVoortzetting van De Vonk,Redactie: Wim Storm (hoofdredacteur), Henriette Roland Holst, Richard Jokel, Jef Last, W. Romeyn"